2013
DOI: 10.1001/jamaophthalmol.2013.1644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Concentrations of Benzalkonium Chloride on Acanthamoebal Survival and Its Potential Impact on Empirical Therapy of Infectious Keratitis

Abstract: The significant antiacanthamoebal effect of benzalkonium chloride, at or below concentrations used for preservation of common ophthalmic preparations, should be understood both when choosing empiric antibiotic therapy for infectious keratitis and when assessing the persistent rise in Acanthamoeba cases in the United States since 2003. Objective: To characterize the antiacanthamoebal efficacy of low concentrations of benzalkonium chloride (BAK) for drug preservation and therapeutic effect against Acanthamoeba. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…In the case of the artificial tear Oculotect®, the preservative agent used is BAK, a known antibiotic and amoebicidal compound [ 20 ]. This study demonstrated that BAK, in its commercially available formulation, maintains good amoebicidal activity despite the other components of the artificial tear and even when the tear is diluted 1:1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of the artificial tear Oculotect®, the preservative agent used is BAK, a known antibiotic and amoebicidal compound [ 20 ]. This study demonstrated that BAK, in its commercially available formulation, maintains good amoebicidal activity despite the other components of the artificial tear and even when the tear is diluted 1:1.…”
Section: Discussionmentioning
confidence: 99%
“…Hard contact lenses adsorb a small amount of this preservative and release a significant percentage of it during a regular washout procedure, approaching the upper safety limit, but soft contact lenses present a high adsorption of this substance. Such a property could allow the accumulation of BAK in the cornea epithelium, producing adverse effects [ 20 ]. Despite BAK’s toxicity, the promising results showed by Oculotect®, its use as a PrEP (pre-exposure prophylaxis) strategy before eye surgery should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, empirical antibiotic treatment with fluoroquinolone drugs or other biocides prior to diagnosis could have an effect on the viability of Acanthamoeba . Aside from the antimicrobial drugs, many ophthalmic preparations utilize benzalkonium chloride (BAC) as a preservative, and it has been shown that BAC is highly toxic to Acanthamoeba 19…”
Section: Introductionmentioning
confidence: 99%